Des jardins artificiels par d'autres stimuli que purement visuels - Laurence Kimmel (Projets de Paysage)
The current trends for hybridization between natural and artificial associated with the loss of control of the city's architecture at large scale lead us to rethink the notion of contemporary garden. Some architects like Philippe Rahm create sensory devices, developed with technical and artificial means, which are not primarily based on the sight perception. The water pavilion he designed in 2008 for the French organization Voies Navigables de France is based on the senses of taste and smell. For Hegel, these "material" senses are less effective at evoking a spatiality than the sight and the hearing. We will discuss in appendix solutions developed in contemporary art.